Conversion of Dioscorea zingiberensis saponins to prosapogenin A by enzymatic hydrolysis. Issue 9 (3rd May 2023) - Yang, Chengyu; Li, Bo; Zhou, Jinwei; Chen, Yufei; Xia, Guohua; Shen, Yuping; Chen, Jixuan; Shao, Jiali; Yang, Yaya; Yang, Huan
Abstract: Prosapogenin A is a secondary saponin in Dioscorea zingiberensis, and it showed remarkable pharmacological effects. Due to very low content and lack of well-developed biotransformation, its preparation was not efficient and clean. This study aims to establish an eco-friendly strategy for preparation of Prosapogenin A from plant material. Physical separation was employed to recycle starch and cellulose, and then D101 resin and polyamide packed-bed column was incorporated for purification of total steroidal saponins (TSS). After these pretreatments, purity of TSS was largely increased to 83.2% with recovery at 87.6%, which was subjected to enzymatic hydrolysis. Optimized reaction system was constructed in 0.20 M HAc-NaAc buffer (pH4.2) containing cellulase/TSS (3:1, w/w ), and the hydrolysis was performed at 53 °C for 6 h. Consequently, TSS was almost completely hydrolyzed to Prosapogenin A, while the highest yield reached 5.62%. The newly proposed approach is promising for efficient preparation of Prosapogenin A in industrial applications. Graphical Abstract: UF0001